2014
DOI: 10.1016/j.postharvbio.2014.05.016
|View full text |Cite
|
Sign up to set email alerts
|

A combined sensory-instrumental tool for apple quality evaluation

Abstract: A combined approach for perceptible quality profiling of apples based on sensory and instrumental techniques was developed. This work studied the correlation between sensory and instrumental data, and defined proper models for predicting sensory properties through instrumental measurements. Descriptive sensory analysis performed by a trained panel was carried out during two consecutive years, on a total of 27 apple cultivars assessed after two months postharvest storage. The 11 attributes included in the senso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
56
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 42 publications
5
56
0
Order By: Relevance
“…Astringency is related to the quantity and quality of phenolic compounds, which are greatly affected by the harvest year (Łata and Tomala 2007, Belviso et al 2013). Corollaro et al (2014) showed that astringency is difficult to predict with instrumental data, but it highly correlates with perceived sourness, an association also observed in the present study.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Astringency is related to the quantity and quality of phenolic compounds, which are greatly affected by the harvest year (Łata and Tomala 2007, Belviso et al 2013). Corollaro et al (2014) showed that astringency is difficult to predict with instrumental data, but it highly correlates with perceived sourness, an association also observed in the present study.…”
Section: Discussionsupporting
confidence: 80%
“…The first PC formed a grainy-juicy-crunchy continuum and the second a sour-sweet continuum, similar to our sensory space of the first and second PCs. The graph by Corollaro et al (2014) showed some year effect, the magnitude and direction of which varied depending on the cultivar, and thus resembled our results considerably.In our PCA, texture attributes loaded on the first and third PC and flavour attributes on the first and second PC. The loading pattern resembled the PCA graph extracted from the storage life data in 2010 (Seppä et al 2013a), which indicated a clear trend towards mealier texture with less flavour intensity during advanced storage time.…”
supporting
confidence: 87%
See 3 more Smart Citations